Handbook of clinical massage : a complete guide for students and professionals - Cassar, Mario-Paul.; Cassar, Mario-Paul.; ScienceDirect eBooks (Edinburgh ; New York : Churchill Livingstone, 2004)
Well researched and evidence-based, this book takes a unique medical approach to describing applied massage techniques for common conditions and their utilization as an adjunct to both conventional and complementary treatments. Offers guidelines on the assessment of each body region prior to massage, including symptoms and signs relating to pathology. Features photographs and line drawings that clearly illustrate correct postural techniques. Thorough descriptions of massage techniques, their physiological effects, indications and contraindications, and how massage may be used therapeutically helps the reader come to a better understanding of the treatment of many common conditions. Each of the chapters on body regions begins with an assessment of the region with guidelines on the examination of pathological symptoms, signs, and implications for massage treatment, preparing the reader for what is to come. A generous number of illustrations, including photographs and line drawings, show the correct techniques for the practitioner. Extra instruction shows supplementary methods for use with patients who are physically impaired, elderly, or unable to lie on the treatment table.
1. The massage treatment -- 2. The massage techniques -- 3. The effects of massage -- 4. The clinical application of massage -- 5. Massage for body regions -- the back -- 6. Massage for body regions -- the lower limb -- 7. Massage for body regions -- the abdomen -- 8. Massage for body regions -- the chest -- 9. Massage for body regions -- the upper limb -- 10. Massage for body regions -- the face, head and neck.
Includes bibliographical references (pages 333-337) and index.
Revised edition of: Handbook of massage therapy : Butterworth-Heinemann, c1999.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Massage therapy -- Handbooks, manuals, etc; Massage -- methods; Massage therapy; Electronic books